English Digital Media Exposure and Receptive L2 Vocabulary Knowledge among Indonesian Adolescents - Naza Fanisa; Alemina Br Parangin-angin (Merwinspy Publisher, 2026)
The increasing availability of English language digital media has transformed language learning experiences among adolescents in non English speaking contexts. This study investigates the relationship between engagement with English digital media and receptive L2 vocabulary knowledge among Indonesian adolescents. Using a correlational descriptive design, the study involved 10 Grade 11 students. Data were collected through a digital media exposure questionnaire and a receptive vocabulary test. The findings indicate that students who reported higher levels of engagement with English digital media tended to obtain higher vocabulary scores. Drawing on Krashen’s Input Hypothesis and multimedia learning theory, the study suggests that digital media may provide meaningful input that supports incidental vocabulary development. However, given the very small sample size and the descriptive nature of the analysis, the results should be interpreted as preliminary and not generalizable. The study highlights the potential value of integrating digital media into English language learning as a supplementary resource alongside classroom instruction.